Induction of anti-herbivore defences by direct amphipod consumption and water borne grazer cues in macroalgae - Cruz, Joana Maria dos Reis Franco (2011)
Dissertação mest., Estudos Marinhos e Costeiros, Universidade do Algarve, 2007